Addressing High Alcohol Consumption and Alcohol Use Disorders Among Adolescents and Young People in Sub-Saharan Africa: Pathways to Effective Action - Turyasiima M; Akot BG; Makongwa I; Yusuf HM; Epuitai J (Substance Abuse and Rehabilitation, 2025)
Munanura Turyasiima,1,2 Balbina Gillian Akot,2 Ibrahimu Makongwa,3 Hamdi Mohamed Yusuf,2 Joshua Epuitai4 1Department of Standards, Compliance, Accreditation and Patient Protection (SCAPP), Ministry of Health, Kampala, Uganda; 2Department of Pediatrics and Child Health, Faculty of Clinical Medicine and Dentistry, Kampala International University, Kampala, Uganda; 3Research and Training Committee, Amana Regional Referral Hospital, Ministry of Health, Dar es Salaam, Tanzania; 4Department of Nursing, Faculty of Health Services, Busitema University, Mbale, UgandaCorrespondence: Munanura Turyasiima, Email tumiek2000@gmail.comBackground: Adolescents and young adults in sub-Saharan Africa face a growing burden of alcohol use and related disorders, driven by a convergence of biological vulnerability, socio-environmental pressures, and weak regulatory systems. Rising digital media exposure and socio-economic disparities further exacerbate risky drinking behaviors.Objective: This review synthesizes current evidence on the prevalence, risk factors, health and social impacts, and intervention strategies related to alcohol use among adolescents and young people in sub-Saharan Africa.Methods: A narrative review approach was employed, drawing on peer-reviewed articles and global reports published between 2000 and 2024. Studies were identified through searches in databases including PubMed, Scopus, Google Scholar, and Web of Science, using defined inclusion criteria focused on youth aged 10– 24 years.Findings: Alcohol use and alcohol use disorders (AUD) among youth are influenced by a complex interplay of genetic, psychological, familial, social, and digital factors. Consequences include increased risks of mental illness, HIV infection, gender-based violence, poor educational outcomes, and long-term health complications. Despite these harms, interventions remain fragmented and under-resourced across much of the region. Promising interventions include school-based programs, community engagement, digital media regulation, and integration of alcohol services into mental and sexual health platforms.Conclusion: Tackling adolescent alcohol misuse in sub-Saharan Africa requires urgent, multisectoral action. Policies must be evidence-based, culturally responsive, and supported by robust surveillance, regulation, and youth-centered programming to prevent long-term public health and socio-economic consequences.Keywords: alcohol use, adolescents, young people, sub-Saharan Africa, alcohol policy, intervention strategies